Ceramika naczyniowa z zamku rycerskiego w Sadłowie, gm. Rypin, woj. włocławskie. Informacje wstępne - Dziubek, Elżbieta (Acta Universitatis Lodziensis. Folia Archaeologica, 1998)
The paper contributes to a preliminary characterization of production technology and assortment of vessels used in Sadłowo castle in Dobrzyń land. The study bases on assemblage of pottery (6580 fragments) gathered during the first season of excavation in 1994. Low frequency of ’’traditional” postsherds (1.7%) and high fraction of fragments from reduced vessels (91.84%; groups B, and C) are features of the material. Low quota of postsherds fired in developed oxidizing atmosphere (4.79%; group D) glazed and the so-called cream ones (1.67% together) supplement a picture of the collection. It is a quite developed assemblage as far as its technology and formal features are concerned. Some of 13.7% of fragments come from wheel-thrown vessels. The most interesting vessels represent forms as folows: a pear-like jug (Tab. X 3), a flask-like vessel (Tab. VII 5), bowls (Tabs. VII, IX, XII), modern bowl with a spout (Tab. XI 1). The materials are preliminary dated from the beginning of the 15th to the half of the 17th century and placed in the second and third stages of the chronology of development of the late medieval pottery according to J. Kruppé. The materials directly harmonizes with the rythm of changes in the northern zone of Brześć Kujawski.